Optimizing Solar Energy Harvesting: An Arduino-Enhanced Dual-Axis Tracking System - Lingam B.; Naresh Yadav Golla; Laxman Vadla; Jagadeeshwar Mangali; Sandhya Gadila; Bharath Teja Kammari; Rao Gundavarpu Mallikarjuna; Maksudovna Vafaeva Khristina (MATEC Web of Conferences, 2024)
Technological progress is enhancing the accessibility and potential of solar energy as a renewable source. This paper introduces a strategy leveraging Ohm's law and the power equation to derive additional energy from solar photovoltaic (PV) panels. The proposed method involves the integration of an automated solar tracking system employing both dualaxis and polar single-axis configurations. This system is comprised of a stationary vertical axis and a flexible horizontal axis, both under motor control. To enhance power output and efficiency, the trackers autonomously follow the sun, constantly adjusting the solar panel positions. The tracking system self-adjusts in the event of a 2 to 3-degree misalignment to minimize power loss due to continuous motor operation. Light intensity sensors analyze illumination levels on each side, guiding the panels toward the light source. The tracking motion continues until equal light exposure on both sides is detected, leading to an enhanced solar irradiance for the panels